Serological Evaluation of Anti-Cyclic Citrullinated Peptide Antibodies and Rheumatoid Factor Titer in a Clinical Population - Auda, Shaimaa Awadh (American Journal of Biology and Natural Sciences, 2026)
Anti-cyclic citrullinated peptide (Anti-CCP) antibodies and rheumatoid factor (RF) are the main serological markers in the diagnosis and follow-up of rheumatoid arthritis (RA). Here we evaluate their prevalence, positivity rates and inter-marker correlation over a 16 month period. A retrospective study was performed on 266 serum samples collected from January 2024 to April 2025, 175 for Anti-CCP and 91 for RF titers. RF positivity was defined as ≥14 IU/mL and anti-CCP positivity as >20 U/mL. Statistical studies included Shapiro-Wilk test of normality, Mann-Whitney U test, chi-square test and Spearman rank correlation.Anti-CCP positive was found in 16% (n=28) of the samples and 44% (n=40) had RF positivity (χ2=23.14, p<0.0001). Both indicators were significantly different in the sero-positive and -negative groups (p<0.000001). The independence of the two markers is supported by the lack of statistically significant association between the two markers (r=0.019, p=0.885). Anti-CCP and RF titers provide complementary diagnostic information in the evaluation of rheumatoid arthritis. The different positive rates and the lack of a relation between the two indicators show the importance of integrated testing in clinical practice.